The Principle of Equality Before the Court in the Systemic Unity of the Instances of the Judicial System of Russia - V. A. Mayboroda; S. I. Shukshin (Теоретическая и прикладная юриспруденция)
The article considers the principle of equality of all before the court. Based on the relationship between the possibilities for ensuring procedural equality in the courts of first and appellate instances, the subsequent assessment of the legality of a judicial act in the courts of cassation and at the stage of supervisory proceedings, the authors came to the conclusion that the existing means of ensuring equality through economic instruments does not fully correspond to the goals of legal proceedings. In this regard, procedural equality between economically strong subjects, economically self-sufficient subjects and other participants in legal proceedings should be ensured by granting a different scope of procedural rights to persons in a worse economic situation relative to the opposite side.